Students’ Mathematical Communication Skills and Their Relation to Self-Confidence in Learning Exponents - Fazira, Lisa; Negara, Habibi Ratu Perwira; Nugraha, Yandika (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematical communication skills are essential for students to understand, construct, and express mathematical ideas. However, studies linking these skills with affective factors such as self-confidence remain limited, particularly in learning exponents. This study aimed to examine the relationship between students’ self-confidence and their mathematical communication skills in exponent learning. A qualitative case study design was applied to 53 eleventh-grade students at SMA Negeri 1 Pringgasela. Data were obtained through a mathematical communication test, a validated self-confidence questionnaire, and in-depth interviews. The results show variations in communication skills across self-confidence levels. Students with high self-confidence communicated ideas more comprehensively through oral, written, and visual representations. Students with moderate self-confidence demonstrated adequate but restricted forms of representation, while those with low self-confidence struggled to articulate ideas consistently. These findings emphasize the significant role of affective factors in shaping mathematical communication. The study suggests that instructional strategies should not only focus on conceptual mastery but also foster students’ self-confidence through collaborative activities, discussions, and presentations. This contributes practically to classroom practice and theoretically to the integration of affective and cognitive aspects in mathematics learning, particularly in the context of exponents.